Recent trends in mortality due to testicular cancer in Ireland: a comparison with England and Wales. Issue 3 (September 1986) - Thornhill, J A; Conroy, R M; Kelly, D G; Walsh, A; Fennelly, J J; Fitzpatrick, J M
Abstract : In the period 1961-84, the number of deaths in Ireland due to the testis cancer rose by 64%. This was due both to significant male population expansion (25.3%) and to an increased mortality rate. In the 25-34 years age group, one of the groups at highest risk, the mortality rate rose by 123%. In contrast, in England and Wales, although the male population has risen by 8.5% since 1961, the number of deaths has decreased by 17%. This is due to falling mortality rates, for example an 18% decrease in those aged 25-34 years. The highest rate of all occurred in those Irish over 75 years old. The changing Irish trends appear to lag behind those in England and Wales by some decades, and this raises important aetiological considerations.